The advantages for the library resulting from the implementation of the project “Higher education in Moldova” by the Ministry of Education and Research of the Republic of Moldova and funded by the World Bank (Bibliouniversitas@ABRM.md, 2025)
This article provides information on the advantages and benefits of the ,,Hîigher Education in Moldova" Project (HEMP) for the users of the Scientific Library of USARB. The benefits will enable the enhancement of institutional capacities in education and research by ensuring an environment conducive to innovation, creativity, and academic excellence. The project supports the continuous updating of study programs in alignment with labor market demands, strengthens partnerships to increase the visibility and appeal of the teaching profession.
Keywords: informational resources; project